Pengembangan Bahan Ajar Praktikum Pengantar Akuntansi Untuk Mahasiswa Jurusan Akuntansi - - Pujiati (Jurnal Ekonomi dan Pendidikan, 2007)
The purpose of this research are: 1. To develop the product of teaching material of introduction to accounting practice for accounting students based on systematic prosedur. It is expected that it will be a understandable teaching material with skill process of competency based approach. 2. To know the use of developing teaching material of introduction to accounting practice in increasing the students ability of introduction to accounting practice of accounting students of STIE Darmajaya Bandar Lampung.The research design uses research and development design (RD). The development that is used is teaching material of introduction to accounting following the Instructional of Development Model (MPI). It consist of 4 steps: first arrangement of GBPP, second arrangement of SAP, third development of teaching material and formatif evaluation. It consist of formative evaluation I it is reviewed by the expert of material and learning designer, formative evaluation II is one by one, formative evaluation III is small group and formative evaluation IV is field try out in the class level.The result of this research and development are: (1) Product of development result that are main students material book, introduction to accounting practice book, guidance and worksheet, lecturer guidance, and accounting learning media that is presented in the form of slide of power point. (2) The result of questionare of learning material expert, learning design expert, students ( in one by one evaluation, small group evaluation, and try out and the lecturer to ward teaching material of introduction to accounting practice) it is known that teaching material is relevant, systematic, well arrange, consistent, appropriate and interesting so it is worth to be used. (3) There is influence in using teaching material of student A and student B majoring D-3 Accounting (STIE Darmajaya Bandar Lampung). After it was examined and it is compare between the group (post hoc test) it is known between the high group in class A with the high in class B there is no differences and also with the average group in class A with the average group in class B there is also no differences and between the low group in class A with the low groups students in class B there is also no differences in their ability. The teaching material of introduction practice of accounting can solve the differences in characterictic and students ability. This is sound with in belt to experience classes, their practice ability of teaching material.